"I beg you...breastfeed the baby, things changed": infant feeding experiences among Ugandan mothers living with HIV in the context of evolving guidelines to prevent postnatal transmission - Emma Dunkley; Scholastic Ashaba; Bridget Burns; Kasey O'Neil; Naomi Sanyu; Cecilia Akatukwasa; Jasmine Kastner; Nicole S. Berry; Christina Psaros; Lynn T. Matthews; Angela Kaida (BMC, 2018)
Abstract Background For women living with HIV (WLWH) in low- and middle-income countries, World Health Organization (WHO) infant feeding guidelines now recommend exclusive breastfeeding until six months followed by mixed feeding until 24 months, alongside lifelong maternal antiretroviral therapy (ART). These recommendations represent the sixth major revision to WHO infant feeding guidelines since 1992. We explored how WLWH in rural Uganda make infant feeding decisions in light of evolving recommendations. Methods We conducted semi-structured interviews with 20 postpartum Ugandan WLWH accessing ART, who reported pregnancy < 2 years prior to recruitment. Interviews were conducted between February-August 2014 with babies born between March 2012-October 2013, over which time, the regional HIV treatment clinic recommended lifelong ART for all pregnant and breastfeeding women (Option B+). Content analysis was used to identify major themes. Infant feeding experiences was an emergent theme. NVivo 10 software was used to organize analyses. Results Among 20 women, median age was 33 years [IQR: 28-35], number of livebirths was 3 [IQR: 2-5], years on ART was 2.3 [IQR: 1.5-5.1], and 95% were virally suppressed. Data revealed that women valued opportunities to reduce postnatal transmission. However, women made infant feeding choices that differed from recommendations due to: (1) perception of conflicting recommendations regarding infant feeding; (2) fear of prolonged infant HIV exposure through breastfeeding; and (3) social and structural constraints shaping infant feeding decision-making. Conclusions WLWH face layered challenges navigating evolving infant feeding recommendations. Further research is needed to examine guidance and decision-making on infant feeding choices to improve postpartum experiences and outcomes. Improved communication about changes to recommendations is needed for WLWH, their partners, community members, and healthcare providers.